MODEL PEMBIAYAAN USAHATANI MELON DI KABUPATEN DELI SERDANG - Desi Novita (AGRIUM: Jurnal Ilmu Pertanian, 2013)
This research is aiming to know the source of financing, and the financing scheme of  melon’s business in the Deli Serdang. The analysis methode used in this research is study case. The Data are taken at the end of 2011. The samples in this research are melon’s farmers around Pantai Labu, Deli Serdang. Primary and secondary data are used in this research. The farming of melon is widely done in Pantai Labu, but still unreach for banking aids. The source of farmer’s financing are from 1) farmer’s own capital, 2)loan from renter with hight rate financing, 3) debt from agriculture store, and 4) the financing from agent. The suitable banking financing scheme for melon’s business is current loan.Keywords : Melon business, financing